Encouraging Walking for Transport and Physical Activity in Children and Adolescents: How important is the built environment? - Giles- Corti, B.; Kelty, S.; Zubrick, Stephen; Villaneuva, K. (Wolters Kluwer Health - Adis International, 2009)
Protected by copyright. Not to be posted on an open-access website